Algorithmic Design Tools in Design Process - Daryanto, Daryanto; Utama, Firza (Bina Nusantara University, 2011)
This article explores algorithmic design methods in a design process that uses natural phenomena as the basis of its architectural morphology. It implements digital morphogenesis in reaction to ecology and the influential forces of the building environment. This paper is divided into two equally important sections: the process description and the project implementation. The description of the process demonstrates the methods used and the idea involved in incorporating nature’s influential elements as part of the creative task. Meanwhile, the project implementation showed practical case of the outcome of that process. Tools for visualizing and simulating nature’s environment are showed using algorithmic design method. The tools create transformations in NURBS-based surfaces through the translation of their respective control point matrices. The tools generate several different alternatives to be tested and analyzed.